Modification of pre-operative order set to reduce PACU stay times for outpatient benign gynecological surgery - Jessica Ainooson; Marcus Alonso Cee Williams; Rulan Yi; Heather Hervey-Jumper; Lee-lynn Chen; Stephanie Lim (PLoS ONE, 2026)
A quality improvement project was implemented at a single medical center’s outpatient benign gynecological surgery division to address prolonged post anesthesia care unit (PACU) stays (defined as greater than 120 minutes). Initial barrier analysis within the department identified gabapentin use in the perioperative setting as a possible contributor. The intervention removed the default pre-op order set of 600 mg gabapentin. One-year post-intervention (baseline n = 281, intervention n = 573) it was observed that the average PACU stay time for benign gynecological surgeries was reduced from an average of ~183 to ~159 minutes marking a 12.6% reduction in PACU stay time (p < 0.0001). Gabapentin use decreased from 92.17% to 1.25% with no change in pain scores. After the intervention, there was no longer a statistically significant difference in PACU stay times by age. This intervention successfully decreased PACU stay times, highlighting pathways to advance individualized, age-conscious care through quality improvement interventions.